Comparative Analysis of Pass Go and Traditional Drill Training Methods on Passing Accuracy Development in Youth Football Players Aged 12-15 Years: A Randomized Controlled Trial - Valerio, Larue; Yagin, Fatma Hilal; Plakias, Spiridon (INSPIREE: Indonesian Sport Innovation Review, 2025)
The  purpose  of  the study. The precision of passing techniques is crucial for young football players, yet empirical comparisons of training methodologies during ages 12 to 15 are lacking. This randomized controlled trial evaluated the effectiveness of the Pass Go methodology, a game-based learning approach, against traditional drill training in enhancing passing accuracy, decision-making speed, and technical execution among youth football players. Materials and methods. Sixty youth football players aged 12-15 were randomly assigned to a 12-week intervention with three groups: Pass Go (game-based training), drill-based training, and a control group. Passing accuracy (short-range and medium-range), decision-making, and technical execution were assessed at baseline, mid-intervention, and post-intervention. Results. During a 12-week intervention, the Pass Go methodology group significantly outperformed the drill-based training group in short-range passing accuracy, improving by 24.3% compared to 19.1% (d=1.82, p<0.001), medium-range passing accuracy with increases of 18.7% versus 15.4% (d=1.56, p<0.001), and decision-making speed, achieving a 64.3% improvement against 33.3% (p<0.001). Age-specific analysis revealed that younger participants (12 to 13 years) exhibited greater technical improvements, while older players (14 to 15 years) showed enhanced decision-making abilities. Both experimental groups significantly outperformed the control group across all parameters measured, confirming their superior efficacy. Conclusions. The Pass Go methodology, emphasizing game-based learning, significantly outperformed traditional training in developing comprehensive passing skills among youth football players. These findings advocate for the enhanced incorporation of game-based learning strategies in youth football programs and stress the need for age-specific adaptations in training design to maximize player development.